Social Support and Depressive Symptoms Among Adolescents During the COVID-19 Pandemic: The Mediating Roles of Loneliness and Meaning in Life - Liu, Ying; Hu, Jinsheng; Liu, Jia (Frontiers in Public Health, 2022)
Identifying which factors influence depressive symptom during the COVID-19 pandemic is highly significant for psychological crisis interventions among adolescents. Social support is likely to be one of the main factors. However, the underlying mechanism is still not well understood in the context of COVID-19. The current study examines whether loneliness and meaning in life mediate the association between social support and depressive symptoms in adolescents. A sample of 1,317 high school students in China were surveyed using the Perceived Social Support Scale, the Chinese Child Loneliness Scale, the Meaning in Life Questionnaire, and the Beck Depression Inventory-II. The results showed that social support predicted depressive symptoms directly and indirectly by enhancing loneliness and diminishing the sense of meaning in life. These findings help in providing new entry points in the design of effective depression prevention and intervention for adolescents during the COVID-19 pandemic.